a) ( – 26 ) – 11 + 2 = x – 1 b) 27 + ( – 15 ) = x + 45

a) ( – 26 ) – 11 + 2 = x – 1

b) 27 + ( – 15 ) = x + 45

2 bình luận về “a) ( – 26 ) – 11 + 2 = x – 1 b) 27 + ( – 15 ) = x + 45”

  1. a) (-26) – 11 + 2 = x-1
    -26-11+2 = x-1
    -37+2 = x-1
    -35 = x-1
    x = -35+1
    x = -34
    Vậy x = -34
    ———————————–
    b) 27 + (-15) = x+45
    27-15 = x+45
    12 = x + 45
    x = 12 – 45
    x = -33
    Vậy x = -33 
     

    Trả lời
  2. Giải đáp+Lời giải và giải thích chi tiết:
    a)
    (-26)-11+2=x-1
    -35-x=-1
    -x=-1+35
    -x=34
    x=-34
    Vậy x=-34
    b)
    27+(-15)=x+45
    27-15=x+45
    12-x=45
    x=12-45
    x=-33
    Vậy x=-33
    $#<33$

    Trả lời

Viết một bình luận

Câu hỏi mới